The forgotten warrior - Hunter, Erin. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
Jayfeather, Lionblaze, and Dovewing face their destinies and an outsider in the ThunderClan turns Clanmates against one another, leading the warrior cats to question who they can trust.
"Warriors adventure game inside"--Back cover.
5.4
5-8
5-8
740L
740L
Keywords: Cats -- Juvenile fiction; Prophecies -- Juvenile fiction; Cats -- Fiction; Prophecies -- Fiction; Cats -- Fiction; Prophecies -- Fiction